Drawing the divide : the nature of Athenian identity as reflected in the depiction of the „other‟ in Attic red-figure vase painting in the fifth century BCE - Moodie, Meg R. (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.